Coating polyvinylchloride surface for improved antifouling property. Issue 4 (4th March 2019) - Wen, Xin; Almousa, Rashed; Anderson, Gregory; Na, Sungsoo; Xie, Dong
Abstract: Antifouling surfaces are specifically crucial to cardiovascular applications. In this study, a polyvinylchloride (PVC) surface was modified by coating a biocompatible and hydrophilic polymer by a mild coating technique. The PVC surface was first activated and then functionalized, followed by coating with the polymer. Results show that the coated hydrophilic polymer significantly reduced 3T3 fibroblast cell adhesion as well as bacteria adhesion. The 3T3 cell adhesion to the polymer-coated surface was reduced to 52–66% as compared to the original PVC surface. Bacterial adhesion to the polymer-coated surface was reduced to 61–80% for Pseudomonas aeruginosa, 65–81% for Staphylococcus aureus, and 73–85% for Escherichia coli, as compared to the original PVC surface. It appears that this novel polymer-coated PVC surface has an antifouling property.